Reliable Fault Tolerance System for Service Composition in Mobile Ad Hoc Network - Veeresh Poola; Praveen Sam R; Shoba Bindu C (Institute of Advanced Engineering and Science, 2019)
A Due to the rapid development of smart processing mobile devices, Mobile applications are exploring the use of web services in MANETs to satisfy the user needs. Complex user needs are satisfied by the service composition where a complex service is created by combining one or more atomic services. Service composition has a significant challenge in MANETs due to its limited bandwidth, constrained energy sources, dynamic node movement and often suffers from node failures. These constraints increase the failure rate of service composition. To overcome these, we propose Reliable Fault Tolerant System for Service Composition in MANETs (RFTSC) which makes use of the checkpointing technique for service composition in MANETs. We propose fault policies for each fault in service composition when the faults occur. Failure of services in the service composition process is recovered locally by making use of Checkpointing system and by using discovered services which satisfies the QoS constraints. A Multi-Service Tree (MST) is proposed to recover failed services with O(1) time complexity. Simulation result shows that the proposed approach is efficient when compared to existing approaches.